Dimensions of Emotional Intelligence and Transformational Leadership: A Correlation Analysis - Ugoani, John N. N. (2015)
The study was designed to explore the degree of relationship between emotional intelligence and transformational leadership style. Goleman who popularized the concept of the science of emotional intelligence and brought it to its academic zenith drew on a wealth of research to argue that successful leaders need emotional intelligence, or the attributes of self-awareness, impulse control, persistence, confidence, self-motivation empathy, social deftness, trust worthiness, adaptability, and a talent of collaboration. Data were generated through 5 – point Likert-type questionnaire based on Schutte, Self Report questionnaire. Pearson’s correlation analysis was carried out through the Statistical Package for Social Sciences, and a strong positive correlation of r = .90, was found between emotional intelligence and transformational leadership style.